2021
DOI: 10.1093/humupd/dmab044
|View full text |Cite
|
Sign up to set email alerts
|

The putative roles of FSH and AMH in the regulation of oocyte developmental competence: from fertility prognosis to mechanisms underlying age-related subfertility

Abstract: BACKGROUND Fertility loss during female ageing is associated with increasing basal FSH and decreasing anti-Müllerian hormone (AMH) concentrations, together with compromised oocyte quality, presumably due to increased oxidative stress (OS) and DNA damage, as well as reduced metabolic and meiotic competences. Basal FSH and AMH circulatory concentrations have been broadly utilized as IVF success predictors, regardless of fluctuations in prognostic accuracy; basal FSH and AMH perform better in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 257 publications
1
13
0
1
Order By: Relevance
“…At the time of ovulation, however, they are lost coincident with meiotic maturation of the oocyte, permanently breaking contact‐based germ‐soma communication in preparation for fertilization. Here, we review studies of the nature of the TZPs and the mechanisms that control their gradual accumulation during growth and rapid loss at ovulation, which we hope will complement insightful recent reviews (Buratini et al, 2022; Li & Albertini, 2013; Robert, 2021).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…At the time of ovulation, however, they are lost coincident with meiotic maturation of the oocyte, permanently breaking contact‐based germ‐soma communication in preparation for fertilization. Here, we review studies of the nature of the TZPs and the mechanisms that control their gradual accumulation during growth and rapid loss at ovulation, which we hope will complement insightful recent reviews (Buratini et al, 2022; Li & Albertini, 2013; Robert, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Here, we review studies of the nature of the TZPs and the mechanisms that control their gradual accumulation during growth and rapid loss at ovulation, which we hope will complement insightful recent reviews (Buratini et al, 2022;Li & Albertini, 2013;Robert, 2021).…”
mentioning
confidence: 96%
“…Otsuka and Shimasaki demonstrated that the mitotic activities of oocyte-derived bone morphogenetic protein-15 and GC-derived kit ligand depend on the oocyte-GC communication system, which may play a pivotal role in ovarian folliculogenesis (122). Additionally, a series of protein and polypeptide hormones secreted by the pituitary gland, such as prolactin (PRL), growth hormone (GH), FSH, and LH, are essential for the activation and initial recruitment of PMFs and the development of growing follicles (123,124). Studies also suggest that cytokines such as epidermal growth factor (EGF), transforming growth factor-alpha (TGF alpha), basic fibroblast growth factor (bFGF), and IGF-1 are involved in folliculogenesis and ovulation (125)(126)(127)(128).…”
Section: Potential Mechanism Of Ovarian Agingmentioning
confidence: 99%
“…It is a good predictor of the damage caused to the ovarian follicles during radiotherapy and chemotherapy [ 8 , 10 , 17 ]. AMH levels are the basis for choosing the right infertility treatment strategy, especially in gonadotropin stimulation during IVF [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%